Gray-Scale Image Colorization Using Various Affinity Functions - Imron Rosyadi (Dinamika Rekayasa, 2012)
In this paper, we have proposed, implemented, and compared some affinity functions for an image colorization algorithm. The colorization qualityof the proposed affinityfunctions was just slightly behind the original functions, while one of the proposed functions performed faster than the original affinity function. We also implemented the colorization algorithm for coloring an Indonesian historical image.